2015
DOI: 10.1044/2015_ajslp-14-0160
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Technology to Promote Functional Communication in Aphasia: Preliminary Evidence From Interactive Dialogues With Human and Virtual Clinicians

Abstract: Purpose: We investigated the feasibility of using a virtual clinician (VC) to promote functional communication abilities of persons with aphasia (PWAs). We aimed to determine whether the quantity and quality of verbal output in dialogues with a VC would be the same or greater than those with a human clinician (HC). Method: Four PWAs practiced dialogues for 2 sessions each with a HC and VC. Dialogues from before and after practice were transcribed and analyzed for content. We compared measures taken before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…There is also evidence suggesting that communication interventions for people with aphasia can be delivered successfully using a non-immersive VR platform [36]. It has been proposed that virtual reality technology in the rehabilitation of patients with aphasia has the potential to provide treatment efficacy given its capacity to simulate activities of daily living [37]. VR also has the potential to be utilised extensively as a platform for home practice to build communication skills and confidence [38][39][40] within a motivating and engaging virtual environment [41].…”
Section: Potential Use Of Virtual Reality In Communication Rehabilitationmentioning
confidence: 99%
“…There is also evidence suggesting that communication interventions for people with aphasia can be delivered successfully using a non-immersive VR platform [36]. It has been proposed that virtual reality technology in the rehabilitation of patients with aphasia has the potential to provide treatment efficacy given its capacity to simulate activities of daily living [37]. VR also has the potential to be utilised extensively as a platform for home practice to build communication skills and confidence [38][39][40] within a motivating and engaging virtual environment [41].…”
Section: Potential Use Of Virtual Reality In Communication Rehabilitationmentioning
confidence: 99%
“…Three studies investigated the effectiveness of AphasiaScripts (Cherney and Halper, 2008 ; Manheim et al, 2009 ; Cherney et al, 2014 ) and found gains for performance within the program and on standardized measures [WAB-R, Communicative Effectiveness Index (CETI, Lomas et al, 1989 ), Quality of Communication Life scale (QCL, Paul-Brown et al, 2003 ), and the Communication Difficulty subscale of the Burden of Stroke Scale (BOSS, Doyle et al, 2004 )]. Another study (Kalinyak-Fliszar et al, 2015 ) investigated a different type of script training treatment to improve production and found improvement in production of the trained scripts and some improvement on discourse narratives.…”
Section: Previous Technology-based Rehabilitation Studiesmentioning
confidence: 99%
“…Of the seven studies that focused treatment on only sentence processing or production (Crerar et al, 1996 ; Linebarger et al, 2007 ; Cherney and Halper, 2008 ; Manheim et al, 2009 ; Thompson et al, 2010 ; Cherney et al, 2014 ; Kalinyak-Fliszar et al, 2015 ), five studies tested and found within task improvement, three studies looked for and found within task generalization, four studies examined and found gains on impairment-based measures while two studies tested and found functional/QOL measurement improvement. Three studies looked for and found maintenance of within task improvement or maintenance of treatment-induced gains on standardized measures.…”
Section: Questions That Can Now Be Examinedmentioning
confidence: 99%
See 2 more Smart Citations